The Effectiveness of Bandotan (Ageratum conyzoides L.) Leaf Extract on Mortality of Boophilus microplus In Vitro - Dwi Retno Widyawati; Iwan Sahrial Hamid; Moh. Sukmanadi; Sri Agus Sudjarwo; Muhammad Hambal (Universitas Airlangga, 2021)
The purpose of this research is to find the effectiveness of bandotan’s (Ageratum conyzoides L.) leaf extract on mortality of Boophilus microplus in vitro and also to get of lethal concentration and lethal time. This research used 125 Boophilus microplus. This research used five treatments, namely neguvon suspensionon (K+), ethanol 1% (K-), 1% concentration (P1), 2% concentration (P2) and 3% concentration (P3). The observation of mortality was done every six hours. Boophilus microplus dies when there is no movement. The data were analyzed using one-way ANOVA and followed by Duncan's Multiple Distance Test. The result is said to be significant if p<0.05. Probit analysis of LC50 is 1.63% at the first hour, 0.85% at the second hour, 0.54% at the third hour, 0.34% at the fourth hour, 0.04% at the fifth hour and 0.04% at the sixth hour, LC90 reached by using 5.6%, 2.9%, 1.8%, 1.2%, 0.16 and 0.16% concentration in 1, 2, 3, 4, 5 and 6 hours, respectively. The LT50 of ethanol 1% (K-) was at 10.142 hours, neguvon suspension on (K+) was at 0.747 hours, 1% concentration (P1) was at 2.184 hours, 2% concentration (P2) was at 1.579 hours, 3% concentration (P3) was at 0.923 hours and LT90 was at 23.734, 1.749, 5.110, 3.695 and 2.159 hours. The conclusion of this study was bandotan’s (Ageratum conyzoides L.) leaf extract was effective as an acaricide based on the mortality of Boophilus microplus.